Epidemiological Aspects of the High Blood Pressure in Occupational Environment : Case of a Bank in Cotonou (Benin) - HINSON, Antoine Vikkey (My University, 2019)
Introduction: Due to the heavy burden of morbidity, mortality, and inability to work, hypertension is a major challenge in the workplace. The purpose of this study was to identify the epidemiological characteristics of hypertension among bank employees in Cotonou. Methodology: This was a descriptive and transversal study of bank workers in Cotonou (Benin). The data were collected using the World Health Organization (WHO) STEPwise questionnaire adapted to our context, as well as blood pressure (BP), weight and abdominal perimeter measurement. Using bivariate and multivariate analysis, we analyzed the risk factor of the HBP. Results: The average age was 37.9 ± 8.6 years; the predominance was with men (52.0%). The prevalence of hypertension was 25.3%. The multivariate analysis showed a significant relationship between the occurrence of hypertension and age (OR=1.08), lack of knowledge about preventive measures against hypertension (OR=4.15), work under pressure (OR=8.01) and obesity (OR=3.12). There is a significant relationship between hypertension and workstation (p=0.0113). Conclusion: Our results should help the bank’s decision-makers to develop a prevention program against hypertension by risk factors.
Keywords: Blood Pressure; Workplace; Risks Factors; Cotonou; Benin